СAT-SCRATCH DISEASE IN CHILDREN - Pikul, K.V.; Kotelevska, T.M.; Tarasenko, K.V.; Lysenko, R.B.; Pryimenko, N.O. (World of Medicine and Biology, 2017)
The relevance of the issue on cat-scratch disease is determined by the widespread prevalence of people’s favorite pet, namely, domestic and stray cats. Noteworthy, a cat is kept by every third family in the United States, and 9 out of 10 families in Australia have a cat. The publications report that in the USA about 25,000 people with filinosis (also known as cat-scratch disease) visit outpatient facilities and up to 2,500 people require hospitalization annually. In European countries the expected incidence of the diseases is 10 cases per 100,000 inhabitants. After pathogens got into skin a primary affect occur and limited necrosis develops, which is surrounded by numerous macrophages, multinucleate giant cells, lymphocytes and eosinophils, forming the regional lymphadenitis. The degree of response to infection depends on the immune status of the individual. The prevalence of cat-scratched children is accounted for 80% of sick people. The most serious forms of the disease occur in immunocompetent individuals (cancer patients, individuals after transplantation, HIV-positive people).